Downregulation of Centaurin gamma1A increases synaptic transmission at Drosophila larval neuromuscular junctions. (29th July 2014) - Homma, Mizuho; Nagashima, Shun; Fukuda, Toshifumi; Yanagi, Shigeru; Miyakawa, Hiroyoshi; Suzuki, Emiko; Morimoto, Takako
Abstract Adequate regulation of synaptic transmission is critical for appropriate neural circuit functioning. Although a number of molecules involved in synaptic neurotransmission have been identified, the molecular mechanisms regulating neurotransmission are not fully understood. Here, we focused on Centaurin gamma1A (CenG1A) and examined its role in synaptic transmission regulation using Drosophila larval neuromuscular junctions. CenG1A is a member of the Centaurin family, which contains Pleckstrin homology, ADP ribosylation factor GTPase‐activating protein, and ankyrin repeat domains. Due to the existence of these functional domains, CenG1A is proposed to be involved in the process of synaptic release; however, no evidence for this has been found to date. In this study, we investigated the potential role for CenG1A in the process of synaptic release by performing intracellular recordings in larval muscle cells. We found that neurotransmitter release from presynaptic cells was enhanced in cenG1A mutants. This effect was also observed in larvae with reduced CenG1A function in either presynaptic or postsynaptic cells. In addition, we revealed that suppressing CenG1A function in postsynaptic muscle cells led to an increase in the probability of neurotransmitter release, whereas its suppression in presynaptic neurons led to an increase in neurotransmitter release probability and an increase in the number of synaptic vesicles. These results suggested that CenG1A functions at both presynaptic and postsynaptic sites as a negative regulator of neurotransmitter release. Our study provided evidence for a key role of CenG1A in proper synaptic transmission at neuromuscular junctions.